Lessons from Paraguay’s 14,000 MW Itaipu Project vis-à-vis Nepal’s 6,720 MW Pancheshwar Project - Pun, Sant Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
If due diligence is not undertaken on the ambiguities prevailing in the Mahakali Treaty and Letters of Exchange of 1996, then Nepal may well end up in a ‘no option trap’ like Paraguay on her 14,000 MW Itaipu, a bi-national hydropower project with Brazil. Twenty-five years after the commissioning of Itaipu, Paraguay is still battling with Brazil on such elementary but vital issues like fair energy price, third party access, parity in project management, etc. Nepal could and should learn lessons from Paraguay’s Itaipu experiences. While Itaipu is primarily a hydropower project, Pancheshwar encompasses wider multipurpose applications. This article, however, limits itself only to the hydropower component of the two projects. DOI: http://dx.doi.org/10.3126/hn.v10i0.7098 Hydro Nepal Vol.10 January 2012 20-23